USER EXPERIENCE: NEW DIGITAL EXPERIENCE YIPY MOBILE APPLICATION SEBAGAI MEDIA KOMUNIKASI DI KAWASAN HUNIAN APARTEMEN ROYAL MEDITERANIA GARDEN RESIDENCES PODOMORO CITY - Aidin, Nurul; Hayati, Suryaning (Jurnal Visi Komunikasi, 2023)
Lack of time and communication channels to facilitate all forms of communication between building management and tenants and other stakeholders, submit complaints, convey ideas, and at the same time for the development of further facilities as well as to maintain harmony between occupants and managers, the P3SRS and managers initiated a communication channel based Digital named Yipy. This application started to be used in September 2021 so the researcher intends to find out the user experience of the application. This research is intended to determine user experience in a digital-based communication framework on the Yipy application in terms of six elements of user experience, namely attractiveness, efficiency, clarity, dependability, stimulation, and novelty. The results of this study are 1) attractiveness, has attractiveness, color, animation, and design attracts attention, is easy to access and the features in it are easy to understand; 2) efficiency, this application is very detailed, precise, fast, and practical because of the realtime response; 3) easy to understand, the application is very useful, especially in payment and complaint activities, and is very user friendly; 4) dependability, the application is safe and predictable; 5) stimulation, users will continue to use the yipy application because through this application they can monitor tenant service requests so that; 6) novelty, as a solution for the transition from conventional services to digital-based services, in the form of innovative, creative and informative services.